2020
DOI: 10.1016/j.conctc.2019.100500
|View full text |Cite
|
Sign up to set email alerts
|

Blocking extracellular Galectin-3 in patients with osteoarthritis

Abstract: ObjectiveThis pilot clinical trial examined the efficacy of blocking extracellular Galectin-3 (Gal-3) with modified citrus pectin (MCP), in patients suffering from knee osteoarthritis (OA).Methods50 patients were randomized in a 1:1 ratio to receive MCP or placebo at a dose of 4 g (5 capsules) twice daily for 12 weeks. Serum Gal-3 levels and OA severity were evaluated at baseline and 12 weeks. Gal-3 levels were detected by sandwich ELISA and OA severity was determined using WOMAC-knee, SF-36, and RAPID3 survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Previous studies have shown that Gal-3 levels increase the risk of OA [5,6]. However, the treatment of OA using MCP is controversial [8,9]. Previous studies of Gal-3 based on animal and in vitro studies of human chondrocytesdid not specify the relationship between Gal-3 levels in human circulation and OA [5,6,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Gal-3 levels increase the risk of OA [5,6]. However, the treatment of OA using MCP is controversial [8,9]. Previous studies of Gal-3 based on animal and in vitro studies of human chondrocytesdid not specify the relationship between Gal-3 levels in human circulation and OA [5,6,8].…”
Section: Discussionmentioning
confidence: 99%
“…However, Zhang et al proved through experiments that MCP can promote the repair of chondrocyte damage in rabbits [8]. In the treatment of patients with KOA, Andrews et al found no signi cant difference in the e cacy between MCP and a placebo, and no signi cant difference in Gal-3 levels between the two groups [9].…”
Section: Introductionmentioning
confidence: 99%
“…Gal-3 has a pivotal role in numerous biological activities, such as powerful regulation of cell adhesion, growth, and apoptosis in synovial fluid and numerous tissues in the body [ 20 ]. Some studies [ 20 , 21 ] describe an association between Gal-3 and degeneratively altered cartilage. This association is explained by the fact that Gal-3 accumulates in chondrocytes with progressive cartilage degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, 15 membros da família das galectinas foram identificados em vertebrados, e eles compartilham similaridades significativas na sequência de aminoácidos que compõem sua estrutura, fato que caracteriza um baixo grau de seletividade de anticorpos capazes de reconhecer estas proteínas, facilitando a reação cruzada destes com diferentes tipos de galectinas (COOPER, 2002). Estes membros podem ser encontrados tanto em ambientes extracelulares quanto intracelular, e apresentam uma diversidade na especificidade de seus ligantes (ANDREWS et al, 2020;HONG et al, 2019;QUEROL CANO et al, 2019). Entretanto, as galectinas apresentam diferenças estruturais entre seus CRDs e estrutura quaternária, o que permite a classificação dessas proteínas em três grupos distintos, ilustrados na Figura 5 (HIRABAYASHI; KASAI, 1993).…”
Section: Galectinas-1 (Gal-1) E O Tecido Muscularunclassified